2015
DOI: 10.1177/0192623315610820
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinomas in Vinylidene Chloride–exposed Male B6C3F1 Mice Are Characterized by Oxidative Stress and TP53 Pathway Dysregulation

Abstract: Vinylidene Chloride (VDC) has been widely used in the production of plastics and flame retardants. Exposure of B6C3F1 mice to VDC in the 2-year National Toxicology Program carcinogenicity bioassay resulted in a dose-dependent increases in renal cell hyperplasia, adenoma, and carcinoma (RCCs). Among those differentially expressed genes between controls and RCC from VDC-exposed mice, there was an overrepresentation of genes from pathways associated with chronic xenobiotic and oxidative stress, as well as c-Myc o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The current study also observed that vorinostat exerts a significant influence in regulating the p53 and MAPK signaling pathway. Previous studies have indicated that both p53 and MAPK signaling pathway are clearly associated with various cellular functions, including apoptosis, cell growth, migration and induction of aging, and serve as key pathways for tumorigenesis and progression in kidney cancers ( 68 , 70 74 ). Therefore, vorinostat may possess an antitumor activity by inhibiting p53 and MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The current study also observed that vorinostat exerts a significant influence in regulating the p53 and MAPK signaling pathway. Previous studies have indicated that both p53 and MAPK signaling pathway are clearly associated with various cellular functions, including apoptosis, cell growth, migration and induction of aging, and serve as key pathways for tumorigenesis and progression in kidney cancers ( 68 , 70 74 ). Therefore, vorinostat may possess an antitumor activity by inhibiting p53 and MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%